Meeting hacks - Ford, Neal; Richards, Mark (O'Reilly Media, Inc., 2018)
Meetings are a necessary evil in an architect's life. This segment delves into some techniques you can use in meetings imposed on you and meetings you impose on others.
Online resource; Title from title screen (viewed June 25, 2018)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos